(untitled) (Palaeohispanica. Review about languages and cultures of Ancient Hispania, 2022)
This paper presents the epigraphic novelties from the peninsular Southwest published between the years 2014 and 2021: fragment of a stele found in Carrapateira (Aljezur, Baixo Alentejo, Portugal); graffiti on a gray ceramic fragment (Porto do Sabugueiro, Salvaterra de Magos, Santarem, Portugal); and another fragment of a stele, found in Monte Gonçalo Eanes (Almodôvar).